Hubungan Literasi Sekolah Terhadap Minat Membaca Pada Siswa Sekolah Dasar - Muhammad Yusnan; Kamasiah Kamasiah; Karim Karim (JURNAL PENDIDIKAN ROKANIA, 2023)
The purpose of this study was to determine the relationship between school literacy and interest in reading in elementary school students. This type of research uses quantitative research. This survey uses a closed survey by distributing questionnaires directly to informants. The purpose of distributing this survey is to ensure that informants obtain complete data about the problem without worrying about the answer. The data analysis technique in this research is the Normality Test and the Linearity Test. The results of this study show that the frequency distribution of the school literacy movement variable is at an interval score of 57.73 ≤ X ≤ 67.36 in the medium category with a frequency of 16 students, while the reading interest variable is at an interval score of 50.00 ≤ X ≤ 59.00 in the medium category with a frequency of 16 students. In a simple correlation analysis between school literacy movement and reading interest there is a strong relationship because the Pearson Correlation value is 0.642 where this value is in the range between 0.61 – 0.80. In addition, the value of the ginifiance is also 0.001 < sig 0.05. There is a significant relationship between school literacy and interest in reading in elementary school students.